Immobilization of S, N-codoped TiO2 nanoparticles on glass beads for photocatalytic degradation of methyl orange by fixed bed photoreactor under visible and sunlight irradiation. (February 2015) - Khalilian, Hajar; Behpour, Mohsen; Atouf, Vajiheh; Hosseini, Seyed Nezam
Graphical abstract: Highlights: Visible-light activity increased dramatically through adding Tu into TiO2 solution. The Tu–TiO2 film represent an anatase structure with particle size around 34–36 nm. The methyl orange was remarkably degraded by immobilized TiO2 on glass beads. The methyl orange was decomposed up to 96% in sunlight irradiation after 2 h. The immobilized Tu–TiO2 on glass beads is highly recommended for water treatment. Abstract: This research focused on photodegradation of organic compound by a fixed bed photoreactor. The photoreactor consists of a cylindrical glass tube, was filled by TiO2 coated glass beads codoped with sulfur and nitrogen (S, N). The photoactive layer of TiO2 was deposited on glass beads using the sol–gel dip-coating technique. The S, N-codoped TiO2 film after thermal treatment at 500 °C for 1 h, was characterized by XRD, XPS, SEM and EDX analyses. The XRD analyses exhibited an anatase structure of TiO2 with particle size about 35 nm. The photocatalytic activity was determined by degradation of methyl orange (MO) (7 mg/L, pH 2). The effective parameters of photocatalyst efficiency were investigated in laboratory and large volume scales under visible and sun light irradiations. The results showed that visible-light photocatalytic activity of TiO2 was extremely increased through adding thiourea (Tu) as a source of nitrogen and sulfur into TiO2 sol, which conducted to degradation of MO solution up to 95% in sunlight irradiation after only 2 h. Overall, the photoreactor of immobilized S, N-codoped TiO2 on glass beads was found to be a promising technology for water treatment.